2021
DOI: 10.3346/jkms.2021.36.e180
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Occurrence of Gastrointestinal Infections after COVID-19 in Korea

Abstract: Background After the global epidemic of coronavirus disease 2019 (COVID-19), lifestyle changes to curb the spread of COVID-19 (e.g., wearing a mask, hand washing, and social distancing) have also affected the outbreak of other infectious diseases. However, few studies have been conducted on whether the incidence of gastrointestinal infections has changed over the past year with COVID-19. In this study, we examined how the incidence of gastrointestinal infections has changed since COVID-19 outbreak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 15 publications
7
51
0
Order By: Relevance
“…Although a statically significant increase was not identified compared to the pre-COVID-19 era, the highest annual incidences for pediatric IBD, CD and UC in this study were all observed in the post-COVID-19 era of 2020. Although there have been studies investigating the changes incidence of other diseases or health conditions (9)(10)(11)(12), no study in Asia has yet investigated the change of incidence in pediatric IBD patients after the COVID-19 pandemic. This study is the first in Asia to investigate the incidence in the pediatric population of IBD after the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a statically significant increase was not identified compared to the pre-COVID-19 era, the highest annual incidences for pediatric IBD, CD and UC in this study were all observed in the post-COVID-19 era of 2020. Although there have been studies investigating the changes incidence of other diseases or health conditions (9)(10)(11)(12), no study in Asia has yet investigated the change of incidence in pediatric IBD patients after the COVID-19 pandemic. This study is the first in Asia to investigate the incidence in the pediatric population of IBD after the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Various changes have occurred in the incidence trends of pediatric diseases due to the recent coronavirus infectious disease 2019 (COVID- 19) pandemic. The increase of childhood obesity and decrease of infection-related systemic diseases is associated with compliance with the quarantine rules and changes in living patterns including increased activities at home (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Fudging the numbers was performed. The post-COVID-19 era may see an increase in norovirus outbreaks once social distancing is relaxed, as norovirus cases generally declined during the pandemic [47]. A rigorous public health approach was fruitful, as has been also detected by others [48], and should be fully applied to environmental public health as well in order to ensure adequate public health action.…”
Section: Discussionmentioning
confidence: 95%
“…This probably results from the stringent polices regarding to the prevention and control of the epidemic of COVID-19 in China. Limitation of direct or indirect contact resulted in the significant decline of COVID-19 and simultaneously hampered the spreading of NoVs as well (Ahn et al, 2021 ; Eigner et al, 2021 ; Farah et al, 2021 ; Lennon et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%